Transformational Leadership and Organizational Culture on Employee Performance: : The Mediating Role of Employee Engagement - Achmad Mohyi (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the influence of transformational leadership and organizational culture on employee performance, with employee engagement serving as a mediating variable. The study is motivated by the importance of employee performance as a strategic factor in maintaining organizational competitiveness, as well as by inconsistencies in empirical findings regarding the roles of leadership and employee engagement in enhancing performance. A quantitative approach with an explanatory research design was employed. Data were collected through an online questionnaire distributed to 85 employees working in service and manufacturing organizations in East Java Province, using purposive sampling based on specific criteria. The research instruments were tested for validity and reliability, and the results indicated that all indicators met the required measurement criteria. Data analysis was conducted using multiple linear regression to examine both direct and simultaneous effects among variables. The findings reveal that transformational leadership does not have a significant effect on employee performance. In contrast, organizational culture is proven to have a positive and significant effect on employee performance. Employee engagement does not show a significant effect on performance and does not function as a mediating variable in the relationship between transformational leadership and organizational culture with employee performance. Furthermore, the simultaneous test results indicate that the three independent variables do not collectively have a significant effect on employee performance. These findings suggest that employee performance is influenced by factors beyond the scope of the research model and highlight that organizational culture plays a more dominant role than transformational leadership and employee engagement within the organizational context examined. This study is expected to contribute both theoretically and practically to the development of more contextual and sustainable human resource management strategies.